Fusions of the feminine and technology : exploring the cyborg as subversive tool for feminist reconstructions of identity - Volschenk, Jacolien (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (English))--University of Stellenbosch, 2009.